DEIXIS ANALYSIS OF STUCK IN THE MIDDLE LYRICS BY BABY MONSTER - Pratiwi, Indriani Citra (ReALL - Research on Applied Linguistics and Literature, 2024)
The objectives of this study are to identify the kinds of deixis used in the song lyrics Stuck in the Middle and to find out the dominant types of deixis used in the song lyrics Stuck in the Middle. This research belongs to qualitative research. The researcher uses the observation method, while the data collection technique is listening and analyzing the songs of “Stuck in the Middle” by Baby Monster. The result of this research is the song lyrics of Stuck in the Middle use all types of deixis. Person deixis almost occurs in every lyric of Stuck in the Middle. There are 95 data of person deixis consisting of first, second, and third person deixis. In addition, the other types such as spatial deixis (7 data) and temporal deixis (3 data) also occur in a song of Stuck in the Middle. Most of the personal deixis in Stuck in the Middle song lyric refer to the speaker itself which are encoded by first singular person deixis like I and My. While for first plural person deixis which are You mostly refer to the speaker.